Frequency of Interferon-Resistance Conferring Substitutions in Amino Acid Positions 70 and 91 of Core Protein of the Russian HCV 1b Isolates Analyzed in the T-Cell Epitopic Context - V. S. Kichatova; K. K. Kyuregyan; N. V. Soboleva; A. A. Karlsen; O. V. Isaeva; M. G. Isaguliants; M. I. Mikhailov (Journal of Immunology Research)
Amino acid substitutions R70Q/H and L91M in HCV subtype 1b core protein can affect the response to interferon and are associated with the development of hepatocellular carcinoma. We found that the rate of R70Q/H in HCV 1b from Russia was 31.2%, similar to that in HCV strains from Asia (34.0%), higher than that in the European (18.0%, p=0.0010), but lower than that in the US HCV 1b strains (62.8%, p<0.0001). Substitution L91M was found in 80.4% of the Russian HCV 1b isolates, higher than in Asian isolates (43.8%, p<0.0001). Thus, a significant proportion of Russian HCV 1b isolates carry the unfavorable R70Q/H and/or L91M substitution. In silico analysis of the epitopic structure of the regions of substitutions revealed that both harbor clusters of T-cell epitopes. Peptides encompassing these regions were predicted to bind to a panel of HLA class I molecules, with substitutions impairing peptide recognition by HLA I molecules of the alleles prevalent in Russia. This indicates that HCV 1b with R70Q/H and L91M substitutions may have evolved as the immune escape variants. Impairment of T-cell recognition may play a part in the negative effect of these substitutions on the response to IFN treatment.